2011
DOI: 10.1155/2011/947838
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Review of Hepatitis C in Heart and Lung Transplantation

Abstract: Hepatitis C (HCV) infection is prevalent in recipients of, and candidates for, solid organ transplants. The outcomes of HCV infection in cardiac and lung transplant recipients have yet to be clearly established, and future prospective studies are needed. In the absence of safe and effective antiviral treatment for HCV infection in heart and lung transplant recipients, the management of these patients remains a challenge and must be considered on an individual basis. Interferon therapy for HCV before transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…Higher MELD scores predict higher postoperative complication rates, including reoperation for bleeding, bacterial infections, and inhospital death [124] . Patients with chronic hepatitis C or chronic hepatitis B should be treated before HTx to avoid antiviral drug intake after HTx which may be associated with graft rejection [125] . Finally, patients with heart failure and irreversible cirrhosis could be offered combined heart and liver transplantation [126] .…”
Section: Heart Transplantationmentioning
confidence: 99%
“…Higher MELD scores predict higher postoperative complication rates, including reoperation for bleeding, bacterial infections, and inhospital death [124] . Patients with chronic hepatitis C or chronic hepatitis B should be treated before HTx to avoid antiviral drug intake after HTx which may be associated with graft rejection [125] . Finally, patients with heart failure and irreversible cirrhosis could be offered combined heart and liver transplantation [126] .…”
Section: Heart Transplantationmentioning
confidence: 99%
“…Furthermore, prospective studies are needed to clarify the influence of HCV seropositivity (present before transplant or acquired with/after transplant) on outcomes, and multicenter, randomized controlled trials are needed to establish optimal pre-and post-transplant approaches to treatment of HCV infection. 53 …”
Section: 329mentioning
confidence: 99%
“…Small studies have suggested that hepatitis C (HCV) patients have comparable after heart transplantation survival to patients without HCV [72,73]. However, in the absence of well tolerated and effective antiviral treatment for HCV in heart transplantation patients, decisions regarding candidacy should be individualized based on synthetic liver function, absence of cirrhosis, portal hypertension and degree of active viral replication.…”
Section: Advances In Determining Prognosismentioning
confidence: 99%